FAUNA DE ESTAFILINÍDEOS (COLEOPTERA: STAPHYLINIDAE) ASSOCIADOS A CARCAÇAS DE SUÍNOS - BRUM, Andrelle Caroline de Souza; PAULA, Michele Castro; EULARIO, Aylson Dailson Medeiros de Moura; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2018)
-